A mixed joint universality theorem for zeta‐functions - Genys, Jonas; Macaitienė, Renata; Račkauskienė, Santa; Šiaučiūnas, Darius (Mathematical Modelling and Analysis, 2010)
In the paper, a joint universality theorem for the Riemann zeta‐function and a collection of periodic Hurwitz zeta‐functions on approximation of analytic functions is obtained. First published online: 10 Feb 2011